Determinants of primary school enrollment in Haiti and the Dominican Republic - Gönsch, Iris; Justus Liebig University Giessen (My University, 2011)
Education is considered an important means of alleviating poverty and of improving an individual´s job and earnings prospects. Nevertheless, in Haiti and the Dominican Republic school enrollment is far from complete and shows notable regional variation. This paper analyzes determinants of primary school enrollment and investigates to what extent differences in schooling are due to individual factors compared to family or community influences. Using data from the Demographic and Health Surveys (DHS) for the two countries for two years each, logistic multilevel regression techniques are applied and the heterogeneity of the data sets is quantified using the median odds ratio (MOR). Results support earlier studies that identify the age of a child and family wealth as some of the most important explanatory variables. Combined with detailed descriptive analysis of the enrollment behavior, late enrollment is recognized as an important driver of low overall participation rates. Other influence factors do not have the same importance in both countries. The MOR indicates that educational enrollment status is determined to a relevant extent by household and community level characteristics and suggests an increase in importance of these higher levels over time.
Keywords: primary school enrollment; household-level; multilevel modeling; Caribbean; education; ddc:370